Effect on lotus leaf for dielectric applications. (2022) - Sivabharathy, M.; Lenin, N.; Kanna, R. Rajesh; Sheik Dawood, M.; Senthilkumar, A.
Abstract: Lotus leaves have received significant attention for multiplicity of application. This study focuses on dielectric applications on lotus leaves. The Lotus leaves (Nelumbo nucifera) were taken from Tamilnadu, South India. After assortment of lotus leaves, the lotus leaves was dried in the sun. Finally Ball milling method was used to powder Sun- dried lotus leaves having thickness of 5(µm) and 50(µm). The Microstructure have been analyzed using scanning electron microscope (SEM) and Fourier-transformed infrared (FTIR) spectroscopy methods. Frequency-dependent dielectric constant (ε′), complex dielectric (ε″) constant and dielectric loss/loss tangent (tan δ) were measured. The results are compared with available literature values and discussed.